Infrapatellar Fat Pad Osteochondroma: Three Cases and a Systematic Review - Evaniew, Nathan; Bayegan, Darius; Popovic, Snezana; Parasu, Naveen; Ghert, Michelle (The Journal of Knee Surgery, 2015)
Extraskeletal para-articular osteochondromas of the infrapatellar fat pad are unique soft-tissue tumors whose etiology and clinical history remain poorly understood. We report three cases and a systematic review of the literature. Three females, aged 47, 54, and 70 years, presented with pain and a parapatellar knee mass. All three underwent marginal excision with no complications and no recurrence. In the literature, 32 reports describing 42 cases were identified. Mean age at presentation was 51.1 years (range: 12–75). There were 25 females and 20 males. Seven patients (15.6%) had a history of antecedent trauma. Mean duration of presenting symptoms was 63.9 months (range: 2–300). All patients except for one underwent open excision. Mean follow-up was 14.9 months (range: 3–96). There were no reports of recurrence or malignant transformation. Para-articular extraskeletal osteochondromas of the infrapatellar fat pad have a benign clinical history regardless of whether they are managed by arthroscopic or open marginal excision.
Keywords: osteochondroma; chondroma; knee; fat pad; surgery